Interview with contemporary Siberian philosopher Fyodor Girenok - Eugenia Ellanskaya (Slovo, 2014)
FYODOR GIRENOK IN CONVERSATION WITH SLOVO’S EXECUTIVE EDITOR EUGENIA ELLANSKAYA Fyodor Girenok is a Professor of Philosophical Anthropology at Moscow State University. He is the leader and founder of the cutting-edge Russian philosophical movement known as archaeo-avantgarde and is one of the most notable Russian philosophers of today. Girenok’s books and articles have been extensively published in Russia, exploring such topics as language, speech, and inter-human communication. Focusing on philosophical anthropology, Girenok’s works address the metaphysics and phenomenology of the human condition and the issues of the crucial relationship with the Other. As well as an innovative thinker in his own right, Girenok provides ingenious discussions of the classical philosophical concepts and debates evoked by Plato, Descartes, Kant, and Hegel, as well as the anthropological ideas of Husserl, Lacan, Foucault, Sartre, and Deleuze. The movement of archaeo-avantgarde is akin to Western postmodernism and considers the past as something to be decoded by avant-garde philosophical thinking. His works (at the moment only available in Russian) are remarkable for the digestible poetic organization of the text itself and for the approachability of the complex discussions evoked. Girenok is a philosopher to be reckoned with, proposing fundamentally new ways of thinking and communicating. As Fyodor’s works remain unpublished in English as of yet, Slovo is introducing to the English-speaking readers a Siberian philosopher that makes a difference. Click here to read article.